(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
دراسة مرض الذبول الفيوزاريومي على نبات الجلاديولس حقليّاً ومخبريّاً من الإجراءات العلمية والتطبيقية لتحسين إنتاجه كمّاً ونوعاً. وقد أظهرت هذه الدراسة النتائج التالية: 1. الصنف White friendship أكثر حساسية للإصابة بالمرض من الصنف Peter pears. 2. الصنف Mascagni هو أكثر الأصناف المدروسة مخبريّاً حساسية للمرض بينما الصنف Priscilla هو الأكثر مقاومة. 3. ينمو الفطر جيداً على المُستنبت P.D.A. ويتبوغ بشكل كبير على مُستنبت المُستخلص. 4. درجة الحرارة 28م0 هي الدرجة المُثلى لنمو الفطر. 5. سرعة تشكل أبواغ الفطر أكبر على المُستنبت P.D.A. 6. بازدياد كثافة المُعلق تنخفض نسبة إنبات أبواغ الفطر. 7. لفطر Fusarium oxysporum مدى عوائلي واسع فهو يُصيب العديد من النباتات التابعة لفصائل نباتية مختلفة. Field and laboratory study of fusarium wilt on gladiolus plants is a scientific and practical measurement for quantity and quality yield improvement. This study showed the following results: 1) The variety White friendship was more susceptible to infection than variety Peter pears. 2) Under laboratory conditions the variety Mascagni showed the highest susceptibility, whereas the variety Priscilla showed the highest resistant. 3) Fungus Fusarium oxysporum f. gladioli grows good on P.D.A. medium and spores excellent on medium extract. 4) Temperature degree 28 Co is the optimal degree for fungus growth. 5) Fungus spore formation is faster on P.D.A. medium. 6) Increasing the concentration of suspension decreases the percentage of fungus spore germination. 7) Fusarium oxysporum has a wide host range and attacks many plants belonging to different plant families.